Productivity of the Czech Republic Measurement at Aggregate and Economy Level Growth of Productivity and Classification of Enterprises - Jangra, Sandeep; Vltavská, Kristýna; Fischer, Jakub, 1978-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The aim of the work I selected this master thesis to work on massive amount of data provided by the Czech Statistical Office (CZSO) and TFP has gained importance as it has been helpful in accelerating the rate of economic growth. Keeping this in mind I identified the importance of having correct measure of productivity for the growth of enterprises, along with list of determinants. I would like to thank Professor Jan Fisher who explained me about the topic. Many researchers had published their research work using multiple methodologies and various inputs, so I would like to contribute my work in identifying productivity of the Czech Republic enterprises with two key determinants. From there my journey to know about TFP started and with my work, I wanted to correctly estimate the productivity growth of the Czech Republic. Lots of complication and concerns were raised and I knew it before taking this thesis, but I kept myself focused on providing nearest correct figures while addressing concerns raised by multiple people. This thesis sets out examine the TFP of the Czech Republic enterprises and its determinants., rather than on output growth. I carefully considered the theoretical links between TFP and two input factors (capital and labour) and one output factor (revenue/value added). Another interesting task assigned along with this topic was to identify incorrectness of data. Although not much work has been done in this direction during implementation but still to a certain point it has been achieved. I also maintained cleanliness of data and reported them to my point of contact in Czech Statistical Office. I aimed to provide relevant theoretical background of total factor productivity growth of enterprises while limiting my thesis to only two factor of inputs – labour and capital. Also, I investigated and tried to find out what are all sectors in the Czech Republic whose productivity, although, decreasing but how deep it dwindles.
Maintaining quality of data and point out data quality issues because incorrect TFP will be generated during analysis. Finally, my ambition was to achieve a result-oriented method and modelled script which can be used after my internship with Czech Statistical Office. The intent was to ensure, model is easily understandable and official users can make changes as per their need. Methods used In general, the TFP measurement methods that has been used in empirical productivity studies can be classified into two groups: conventional or non-frontier methods and frontier methods. In this thesis, I implemented conventional method – or general model of Cobb-Douglas production function. Although there are lots of assumption has been made while considering this method. Important and foremost assumption is that outputs are efficiently produced on the production frontier. Furthermore, conventional method can be further classified into parametric and nonparametric, and here I selected parametric approach. Reason being, with parametric approach, I can impose well adopted functional form of production function and employs econometric techniques in estimating production function. Data from Czech Statistical Office were having limited number of determinants so selecting Cobb-Douglas production function is the best approach. In examining TFP determinants, methods selected should decomposed into embodied technical changes. Technical change is referred to as change that is captured in factor inputs, such as labour, capital, improved machinery, new quality of intermediate goods, and other inputs. There was always a trade off using one output over another. Researchers give preference turnover as output rather than value added; however, this can be another way as well. In implementation of method, both figures were generated, one based on turnover and another on value added. Output is way different because former consider intermediate as factor of input while value added omits it. It
Vedoucí práce: Kristýna Vltavská
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: official statistics [obor dipl. práce]; diplomové práce; master's theses